Analisis Maqashid atas Arah Kebijakan Ekonomi Syariah Era Reformasi Indonesia - Faridatuz Zakiyah; Mohammad Salahuddin Al-Ayyuubi (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2025)
This study comparatively analyses the direction of Islamic economic policy in Indonesia during the Reform era (1998-2024) through the framework of Maqashid al-Shari’ah. Using a qualitative literature study method with a deductive content analysis approach, this research maps the policy evolution across five presidential administrations: B.J. Habibie, Abdurrahman Wahid, Megawati Soekarnoputri, Susilo Bambang Yudhoyono, and Joko Widodo. The findings reveal a progressive policy trajectory, shifting from a focus on fulfilling essential needs (dharuriyyat) in the early Reform era, such as establishing the legal framework for Islamic banking, to fulfilling secondary needs (hajiyyat) through institutional strengthening and comprehensive legislation, and ultimately reaching the complementary level (tahsiniyyat) with a focus on ecosystem integration, industry consolidation, and global innovations like Green Sukuk. The analysis indicates the dominance of the pillars of preserving wealth (hifz al-mal) and religion (hifz al-din), while also highlighting challenges in translating the substance of Maqashid to the operational level. The contribution of this research is to provide a Maqashid-based policy analysis model and recommendations for aligning future policies to be more holistic.